Prevalence of Self-Medication and Assessment of its Consequences on Health among Female University Students in Islamabad, Pakistan - Eshrat Abbas,; Rabia Gul,; Adil Hussain, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Self-medication (SM) is the drug attainment and consumption without consulting a doctor/physician against a particular disease. This cross-sectional study assessed SM and its consequences among the female students of the International Islamic University Islamabad (IIUI), Pakistan. A total of 180 female students from different academic departments were selected on the basis of stratified random sampling technique and the collection of data on SM was done with a pre designed questionnaire. Findings displayed that the prevalence of SM among the female students of IIUI, Islamabad, Pakistan was 32.22 to 55.6%. The information source of medicines in students was 48.9 % from doctors/physicians and 33.9% from the internet. The disease conditions for which SM was adapted includes headache, flue, cough and cold in about 64.4% students and abdominal pain in 38.3% students. The most common medicines used for SM were pain killers for 49.4% students, vitamin supplements for 30.6% students and antibiotics for 16.7% students. About 46.1% students obtain medicines for SM from the medical stores and 33.3% obtain from hospitals pharmacy without doctors/physician’s prescription. Majority were using medicines for seasonal (40%) or viral (21.7%) infections or during accidental cases (26.1%). Overall, 68.88% students confirmed that they experienced adverse effects on health after SM. 74.35% students felt some common side effects, 67.16% experienced drug/medicine resistance against other diseases and 58.06% experienced poor immune system due to SM. In this regard, medication through regular consultations with doctors/physicians is necessary and the execution of proper policies on advertising, marketing and selling of medicines with precautionary measures is recommended to avoid adverse effects on health.